Leadership Regeneration Strategies at Al Mizan and Darussalam Pandeglang Islamic Boarding Schools: A Comparative Case Study - Suryapermana, Nana; Fauzi, Anis; Dawam, Badru; Subekhan, Moch.; Lugowi, Rifyal Ahmad (Tadbir : Jurnal Studi Manajemen Pendidikan, 2025)
How is the leadership regeneration process at Al Mizan Modern Islamic Boarding School and Darussalam Modern Islamic Boarding School, and what factors support and hinder the implementation of leadership regeneration at Al Mizan Modern Islamic Boarding School and Darussalam Modern Islamic Boarding School in Pandeglang. This study uses qualitative methods. Data collection uses observation, interview, and documentation techniques. The results of the study show that the leadership regeneration pattern is different in each Islamic boarding school. Al Mizan Modern Islamic Boarding School adopts an open management leadership regeneration pattern, while Darussalam Modern Islamic Boarding School adopts a combination of inheritance systems and inserts an open management pattern on the other side. The regeneration process at the Al Mizan Modern Islamic Boarding School is carried out through the instillation of values, delegation & job descriptions, recruitment of experts, scholarships, developing HR skills, and complex staffing, while the leadership regeneration process at the Darussalam modern Islamic boarding school is carried out through education, and instilling values in good examples and role models. The novelty of this research is that the Al Mizan Pandeglang Modern Islamic Boarding School has carried out the ideal leadership cadre process, while the Darussalam Modern Islamic Boarding School is still in the pioneering phase towards the ideal leadership cadre formation of Islamic boarding schools.